2008
DOI: 10.1002/dvdy.21436
|View full text |Cite
|
Sign up to set email alerts
|

PDGF‐B signaling is important for murine cardiac development: Its role in developing atrioventricular valves, coronaries, and cardiac innervation

Abstract: We hypothesized that PDGF-B/PDGFR-␤-signaling is important in the cardiac contribution of epicardiumderived cells and cardiac neural crest, cell lineages crucial for heart development. We analyzed hearts of different embryonic stages of both Pdgf-b؊/؊ and Pdgfr-␤؊/؊ mouse embryos for structural aberrations with an established causal relation to defective contribution of these cell lineages. Immunohistochemical staining for ␣SMA, periostin, ephrinB2, EphB4, VEGFR-2, Dll1, and NCAM was performed on wild-type and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 57 publications
(87 reference statements)
1
55
0
Order By: Relevance
“…PDGFR-␣ is important mainly for nonneuronal cardiac neural crest development (Morrison-Graham et al 1992). PDGFR-␤ and PDGF-B appear to play a role in neuronal cardiac neural crest development, as both PDGFR-␤ and PDGF-B knockouts display abnormal cardiac innervation (Van den Akker et al 2008). Thus, PDGFR-␣ and PDGFR-␤ signaling appear to have complementary roles in cardiac neural crest development.…”
Section: Role Of Pdgf Signaling In Gastrulation and Formation Of Cranmentioning
confidence: 99%
See 2 more Smart Citations
“…PDGFR-␣ is important mainly for nonneuronal cardiac neural crest development (Morrison-Graham et al 1992). PDGFR-␤ and PDGF-B appear to play a role in neuronal cardiac neural crest development, as both PDGFR-␤ and PDGF-B knockouts display abnormal cardiac innervation (Van den Akker et al 2008). Thus, PDGFR-␣ and PDGFR-␤ signaling appear to have complementary roles in cardiac neural crest development.…”
Section: Role Of Pdgf Signaling In Gastrulation and Formation Of Cranmentioning
confidence: 99%
“…Studies using PDGFR-␣ signaling mutants implicate both Src and PI3K as critical mediators of OP proliferation (Klinghoffer et al 2002). Transgenic mice expressing different amounts of PDGF-A in the CNS have revealed that OPs proliferate until the growth factor becomes limiting; i.e., when OPs "consume" PDGF-A at a faster rate than it is produced (van Heyningen et al 2001). When available PDGF is limiting (or withdrawn experimentally), OPs differentiate into myelinating oligodendrocytes.…”
Section: Role Of Pdgfs In Glial Cell Development and Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, pdgfrβ is expressed in the epicardium of developing embryonic mouse hearts and is required for coronary artery formation (21,22). The expression of pdgfrβ in the wound and the epicardium (Fig.…”
Section: Mural Cells Are Present In Coronary Vessels During Zebrafishmentioning
confidence: 99%
“…This is also supported by studies using transgenic mice [11]. We have shown that the sinus venosusderived endothelial cells express the "arterial" Notch1, underlining the plasticity of these cells [9]. The discussion on the origin of the coronary endothelium is kept alive as specific compartments produce restricted numbers of ECs [12,13].…”
Section: Endothelial Cellsmentioning
confidence: 80%